Regulatory T cells and systemic vasculitis. Issue 1 (20th January 2023) - Mirouse, Adrien; Cacoub, Patrice; Saadoun, David
Abstract : Purpose of the review: Emerging data suggest that regulatory T-cells (Treg) alterations play a major role in systemic vasculitis pathophysiology. We performed a systematic review of recent advances in the role of Treg and interleukin (IL)-10 in the pathogenesis and treatment of systemic vasculitis, including giant cell arteritis (GCA), Takayasu arteritis, Behçet's disease, antineutrophil cytoplasm antibodies (ANCA) associated vasculitis (AAV), and cryoglobulinemia associated vasculitis. Recent findings: Emerging data suggest that Treg deficiencies are disease-specific, affecting distinct pathways in distinct vasculitides. Decreased peripheral blood frequencies of Treg are described in all vasculitis when compared to healthy donors. Altered Treg functions are reported in GCA, Takayasu arteritis, AAV, and Behçet's disease with different mechanisms proposed. Treatment with biologics, and sometimes other immunosuppressants, may restore Treg frequencies and/or immune activity with significant differences in active disease or disease in remission in several systemic vasculitis. IL-10 is elevated in GCA, AAV, cryoglobulinemia associated vasculitis. In Behçet's disease, IL-10 is decreased in peripheral blood and elevated in saliva. In Takayasu arteritis, IL-10 levels were essentially elevated in patients' vessel wall. Several new therapeutic approaches targeting Treg and Il-10 (low dose IL-2, CAR Treg…) are developed to treat patients with systemic vasculitis. Summary: Treg and IL-10 play a central role in the regulation of inflammation in vasculitis and new targeting approaches are emerging.